Coenosia Meigen (Diptera: Muscidae) from Angola: new species and records - Couri, Marcia S.; Pont, Adrian C. (Zootaxa, 2016)
The study of unidentified material from Angola (Africa), deposited in the collection of the Natural History Museum, London, United Kingdom, has revealed three new Coenosia species: Coenosia lucens sp. nov., Coenosia flavohumeralis sp. nov. and Coenosia setosa sp. nov., and five new records: Coenosia macrochaeta (Emden, 1940), Coenosia nodosa Stein, 1913, Coenosia ochroprocta (Speiser, 1910), Coenosia planifrons Stein, 1913 and Coenosia translucida (Emden, 1940). Only one species of Coenosia had previously been recorded from Angola: Coenosia sanguenguei Zielke 1971. The new species are described with illustrations of the male terminalia, and diagnoses of the newly-recorded species with descriptions of the male terminalia are given. A list of all Muscidae species recorded from Angola is presented.